(untitled) (Agro-Science Letters, 2026)
Global atmospheric loading of greenhouse gases (GHGs) is intensifying at measurable annual rates: carbon dioxide (CO2) at 0.5%, methane (CH4) at 0.6%, and nitrous oxide (N2O) at 0.25 ppbv yr-1. Farming operations collectively account for roughly 20% of this emission burden, and land-use transformations—especially forest clearance—add another 14% to the total. Among the practices most responsible for carbon release from managed soils are tillage-based soil disturbance, agrochemical inputs, open field burning of harvest residues, and exportation of crop biomass. Cumulative land degradation since the advent of agriculture has eliminated an estimated 55–100 Pg from the global soil carbon pool and 100–150 Pg from terrestrial biotic stocks. Transitioning to scientifically guided management can restore soil organic carbon (SOC) and rebuild degraded land productivity. Under unmitigated warming scenarios, global crop production could fall by a quarter overall, and rain-fed cropping systems—which sustain the world’s most food-insecure populations—could face yield losses approaching 50%. Marginal and smallholder farmers, operating on limited land and capital, face heightened exposure to these disruptions. Concurrent declines in crop yields and freshwater accessibility are anticipated as thermal regimes shift and seasonal precipitation becomes less reliable. This review synthesizes current understanding of SOC behavior under climate pressure and makes the case for scientifically robust policy frameworks that strengthen irrigation systems and safeguard water resources. Decarbonizing the global energy base remains the definitive long-run solution, but soil-based carbon sequestration serves as an indispensable near-term strategy during the transition.